Origin of clear ferromagnetism for p-type GaN implanted with Fe+ (5 and 10 at. %) - Shon, Yoon; Lee, Sejoon; Jeon, H. C.; Park, Y. S.; Kim, D. Y.; Kang, T. W.; Kim, Jin Soak; Kim, Eun Kyu; Fu, D. J.; Fan, X. J.; Park, Y. J.; Baik, J. M.; et al. (AMER INST PHYSICS, 2006)
The systematic enhancement of ferromagnetic hysteresis loops for GaN implanted with high doses of Fe (5 -> 10 at. %) takes place with an increase in the annealing temperature from 700 to 850 degrees C. The trends of magnetic properties coincide with the results of the increased full width at half maximum of triple axis diffraction for GaN (0002), including the appearance of GaFeN, the enhanced Fe-related photoluminescence transitions, and the systematic increase in sizes of symmetric spin ferromagnetic domains GaFeN in atomic force microscopy and magnetic force microscopy. (c) 2006 American Institute of Physics.
Keywords: ROOM-TEMPERATURE FERROMAGNETISM; MAGNETIC SEMICONDUCTORS; MN; IONS